AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN DAN KULIT BATANG BERENUK TERHADAP Bacillus cereus - Devi Nisa Hidayati; Cicih Sumiarsih; Umroh Mahmudah; Anita Dwi Puspitasari (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2018)
ABSTRACTThe plants (Crecentia cujete Linn) Are known to have antibacterial activity and can be used as a diarrhea drug due to microorganisms. Bacillus cereus is one of the bacteria that causes diarrhea.This aims to the study was antibacterial activity of ethanol extract of leaves (EL) and bark broodstock (EB) on Bacillus cereus. EL and EB were extracted with ethanol 96% using maceration method. Antibacterial activity test was carried out with disk diffusion method in EL with a concentration of 30%, 60%, 90%, 120% and 150%, and in EB using concentrations of 60%, 70%, 80%, 90% and 100% then antibacterial activity measurements were taken. by looking at the Diameter of the Inhibitory Area (DDH). The results of the EL and EB of antibacterial activity proved that EL and EB berenuk have antibacterial activity against Bacillus cereus.Keywords: Antibacterial, Crescentia cujete Linn, Bacillus cereus.